Low intake of iodized salt and iodine containing supplements among pregnant women with apparently insufficient iodine status - time to change policy? - Shani R. Rosen; Yaniv S. Ovadia; Eyal Y. Anteby; Shlomo Fytlovich; Dorit Aharoni; Doron Zamir; Dov Gefel; Simon Shenhav (BMC, 2020)
Abstract Background Iodine is an essential nutrient for human health throughout the life cycle, especially during early stages of intrauterine life and infancy, to ensure adequate neurocognitive development. The growing global reliance on desalinated iodine-diluted water raises the specter of increased iodine deficiency in several regions. The case of Israel may be instructive for exploring the link between iodine status and habitual iodine intake in the setting of extensive national reliance on desalinated water. The aim of this study was to explore the relationship between iodine intake, including iodized salt and iodine-containing supplements intake, and iodine status among pregnant women residing in a sub-district of Israel that is highly reliant on desalinated iodine-diluted water. Methods A total of 134 consecutive pregnant women were recruited on a voluntary basis from the obstetrics department of the Barzilai University Medical Center during 2018. Blood was drawn from participants to determine levels of serum thyrotropin (TSH), thyroid peroxidase antibodies (TPOAb), thyroglobulin antibodies (TgAb) and thyroglobulin (Tg). An iodine food frequency questionnaire (sIFFQ) was used to assess iodine intake from food, IS and ICS. A questionnaire was used to collect data on demographic and health characteristics. Results A total of 105 pregnant women without known or reported thyroid disease were included in the study. Elevated Tg values (≥ 13 μg/L), were found among 67% of participants, indicating insufficient iodine status. The estimated iodine intake (median, mean ± SD 189, 187 ± 106 μg/d by sIFFQ) was lower than the levels recommended by the World Health Organization and the Institute of Medicine (250 vs. 220 μg/day respectively). The prevalence of iodized salt intake and iodine containing supplement intake were 4 and 52% (respectively). Values of Tg > 13 μg/L were inversely associated with compliance with World Health Organization and Institute of Medicine recommendations. Conclusions While the Israeli Ministry of Health has recommended the intake of iodized salt and iodine containing supplements, this is apparently insufficient for achieving optimal iodine status among Israeli pregnant women. The evidence of highly prevalent probable iodine deficiency in a sample of pregnant women suggests an urgent need for a national policy of iodized salt regulation, as well as guidelines to promote iodine containing supplements and adherence to them by caregivers. In addition, studies similar to this one should be undertaken in additional countries reliant on desalinated iodine-diluted water to further assess the impact of desalinization on maternal iodine status.